APPLICATION OF COW MANURE, UREA AND NPK FERTILIZER COMBINATION ON THE GROWTH OF PALM OIL (Elaeis guineensis Jacq) IN PRE-NURSERY - Setyawan, Heri; Rohmiyati, Sri Manu; Purba, Jhon Hardy (Universitas Panji Sakti, 2020)
Seedling performance is a prerequisite for successful palm oil cultivation. Determining the growth of seedlings in addition to genetic factors can also be influenced by the provision of nutrients at the beginning of growth. This research was conducted with the aim to get the best combination of cow manure with urea and NPK on the growth of oil palm seedlings in pre-nursery. This experiment used a factorial design, consisting of a single factor arranged in a completely randomized design (CRD), which is a combined application of cow manure, urea fertilizer and NPK fertilizer consisting of 4 combination levels (0.4 g urea + 0.4 g NPK; 0.2 g urea + cow manure fertilizer, 0.2 g NPK + cow manure fertilizer, and 65 g cow manure fertilizer). Research data was analyzed using Analysis of Variance (ANOVA) at 5% significance level. The results showed that administration of a combination of 0.2 g urea + 40 g cow manure produced the best growth of oil palm seedlings, although it had the same effect as a combination of 0.4 g NPK fertilizer + 50 g cow manure, whereas the combination treatment of 0.4 g urea + 0.4 g NPK fertilizer and 65 g cow manure treatment resulted in lower growth of oil palm seedlings.DOI: 10.37637/ab.v3i1.419